Pd(II)-Catalyzed gamma-C(sp(3))-H alkynylation of amides: selective functionalization of R chains of amides (RC)-C-1(O)NHR - Landge, Vinod G.; Parveen, Ayisha; Nandakumar, Avanashiappan; Balaraman, Ekambaram (Chemical Communications, 2018)
The gamma C(sp(3))-H bond alkynylation of R chains of amides (RC)-C-1(O)NHR, a fundamental class of synthetic substrates, has not been accomplished to date. Here, the first example of palladium(ii)-catalyzed alkynylation of an unactivated gamma C(sp(3))-H bond of alkyl amides (cyclic, linear, and amino acids) is reported. The kinetic experiment shows that the rate of the reaction depends on the coupling partners and the amides. Late-stage diversification of alkynylated amides was developed by utilizing amine and alkyne functionalities.